Intrahousehold empowerment gaps and dietary diversity in China - Huang, Yanfang; Yang, Yuying; Nie, Fengying; Jia, Xiangping (Frontiers in Nutrition, 2024)
This article analyzes the relationship between intrahousehold empowerment gaps and food and nutrition security using quantitative data collected through a household survey organized by the Agricultural Information Institute, Chinese Academy of Agricultural Sciences (CAAS-AII), in 2023.Based on empowerment theory, this study measured the relative empowerment of spouses from the Abbreviated Women's Empowerment in Agriculture Index (A-WEAI). From the micro-level evidence of 468 rural households, this study found that intrahousehold empowerment gaps harm the diversity of household diets. In particular, reducing gender gaps in access to resources, leadership, and income can help diversify household diets. However, data on the impact of shortening the difference in working hours between wives and husbands for the benefit of food safety are yet to be conclusive. Additionally, gender gaps in the group of non-coresident mothers-in-law and nonmigrants hurt household food security. The paper also provides further justification for policies and interventions that aim to improve women's bargaining position in the household.